The Paradox of Decentralization: Centralized Administrative Governance during the New Order Era in Indonesia - Mudhoffar, Khosyi; Frinaldi, Aldri; Magriasti, Lince; Naldi, Hendra (Universitas Pahlawan Tuanku Tambusai, 2025)
This article examines the implementation of decentralization and public administration management during Indonesia’s New Order era, focusing on how decentralization was practiced within a highly centralized power structure. Based on a qualitative literature review and content analysis of secondary sources, including government regulations, policy documents, and academic studies, the research explores the gap between the formal narrative of regional autonomy and the reality of central control. It is found that although the legal framework for regional autonomy was established through Law No. 5 of 1974, the actual governance practice centralized decision-making in the hands of the central government. The New Order regime employed administrative decentralization and developmentalist ideology to legitimize central control over local governments. The military's involvement in local bureaucracy and the absence of local democracy further reinforced centralization. This centralized legacy has had a long-term impact on the capacity and quality of regional governance in the post-reform era. Therefore, decentralization in Indonesia requires deep structural and cultural reforms to realize democratic and effective regional autonomy